Starch-containing resin composition

The starch-containing resin composition, featuring a thermoplastic resin, starch, and starch-containing lubricant, addresses issues of low productivity and poor dispersibility, while suppressing bleed-out to enhance the quality of molded products.

JP7653253B2Active Publication Date: 2025-03-28NAGASE & CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020214461
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2025-03-28
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

Existing starch-containing resin compositions face challenges with low productivity due to the low bulk density of powdery starch, poor starch dispersibility caused by strong self-cohesion forces, and issues with starch plasticizer bleed-out leading to stickiness and printing defects.

Method used

A starch-containing resin composition that includes a thermoplastic resin, starch, and a starch-containing lubricant, such as a surfactant or starch plasticizer, with a starch content ratio of 10% to 70% by weight. The composition also optionally includes a water-soluble polysaccharide like pullulan or dextrin, which improves starch dispersibility and stability.

Benefits of technology

The proposed composition achieves excellent starch dispersibility and suppresses bleed-out, resulting in improved productivity and quality of molded products with reduced stickiness and printing defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653253000005
    Figure 0007653253000005
  • Figure 0007653253000001
    Figure 0007653253000001
  • Figure 0007653253000002
    Figure 0007653253000002
Patent Text Reader

Abstract

To provide a starch-containing resin composition which enables production of a molding that is excellent in dispersibility of starch, and suppresses bleed-out.SOLUTION: A starch-containing resin composition contains a thermoplastic resin, starch and a lubricant for starch, in which the lubricant for starch is at least one selected from the group consisting of a surface active agent and a plasticizer for starch, a content ratio of the starch in the starch-containing resin composition is 10 wt.% to 70 wt.%, and when a press flat plate with a thickness of 0.1 mm formed from the starch-containing resin composition is formed, the number of impurities of 0.3 mm2 or more observed on the surface of the press flat plate is 4 or less per area of 2,500 mm2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a starch-containing resin composition. [Background technology]

[0002] In recent years, many compositions have been proposed in which organic or inorganic fillers are mixed with biodegradable resins or thermoplastic resins. Among these fillers, starch is a relatively inexpensive organic filler, and thermoplastic resin compositions containing starch as an extender, a bio-degree improver, or a biodegradation promoter for the biodegradable resins or thermoplastic resins (hereinafter also referred to as starch-containing resin compositions) have attracted attention. Patent documents 1 to 4 propose resin compositions containing thermoplastic resins and starch, but when powdered starch is supplied to a melt kneading device (a representative example of which is an extruder) and melt-blended to obtain a composition, the starch is a powder with a low bulk density, so it is not easy to supply it to the melt kneading device, and the productivity of the starch-containing resin composition is extremely low. In addition, the starch-containing resin composition has a problem that it is not easy to disperse starch well in a resin matrix due to the strong self-aggregation force of starch. For example, there is no detailed description of starch dispersibility in Patent Document 1. In addition, glycerin and polyethylene glycol, which are used as starch plasticizers, have the effect of increasing the dispersibility of starch, but a large amount of them may need to be added to exert their function, and the starch plasticizer may bleed out from the starch-containing molded body, causing problems such as stickiness and poor printing. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2009-120651 A [Patent Document 2] Patent No. 3477440 [Patent Document 3] Patent No. 4364435 [Patent Document 4] Patent No. 2961135 Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the above problems, and an object of the present invention is to provide a resin composition containing starch, which has excellent dispersibility of starch and enables the production of a molded article in which bleed-out is suppressed. [Means for solving the problem]

[0005] The starch-containing resin composition of the present invention comprises a thermoplastic resin, starch, and a starch lubricant, the starch lubricant being at least one selected from the group consisting of a surfactant and a starch plasticizer, the content of the starch in the starch-containing resin composition being 10% by weight to 70% by weight, and when a press plate having a thickness of 0.1 mm is formed from the starch-containing resin composition, a 0.3 mm thick starch-containing resin composition having a thickness of 0.3 mm thick is observed on the surface of the press plate. 2 The above debris has an area of ​​2500 mm 2 No more than four per range. In one embodiment, the starch-containing resin composition further contains a water-soluble polysaccharide. In one embodiment, the content of the water-soluble polysaccharide is 0.01 parts by weight to 5 parts by weight relative to 100 parts by weight of the solid content in the starch-containing resin composition. In one embodiment, the water-soluble polysaccharide is at least one selected from the group consisting of pullulan and dextrin. In one embodiment, the content of the starch lubricant is 0.01 parts by weight to 5 parts by weight based on 100 parts by weight of the solid content in the starch-containing resin composition. In one embodiment, the surfactant is at least one selected from the group consisting of polyhydric alcohol fatty acid esters, polyglycerin fatty acid esters, and alcohol esters of condensed hydroxy fatty acids. In one embodiment, the starch plasticizer is at least one selected from the group consisting of ethylene glycol, propylene glycol, glycerin, and sorbitol. In one embodiment, the starch is pregelatinized starch. In another aspect of the present invention, there is provided a method for producing the starch-containing resin composition, comprising melt-kneading a thermoplastic resin with a starch granule, the starch granule containing the starch, the starch lubricant, and a water-soluble polysaccharide, the content of the water-soluble polysaccharide being 0.1 to 10 parts by weight relative to 100 parts by weight of the starch, and the content of the starch lubricant being 0.1 to 10 parts by weight relative to 100 parts by weight of the starch. In another aspect of the present invention, there is provided an injection molded article formed from the above starch-containing resin composition. In another aspect of the present invention, there is provided a sheet formed from the above-mentioned starch-containing resin composition. In another aspect of the present invention, there is provided a film formed from the above-mentioned starch-containing resin composition. In another aspect of the present invention, there is provided a sheet-shaped product formed from the above-mentioned starch-containing resin composition. In another aspect of the present invention, there is provided a foamed molded article formed from the above starch-containing resin composition. Effect of the Invention

[0006] According to the present invention, it is possible to provide a resin composition containing starch, which has excellent dispersibility of starch and enables the production of a molded article in which bleed-out is suppressed. [Brief description of the drawings]

[0007] [Figure 1] 1(a) is a photograph showing the appearance of the sheet obtained in Example 1. FIG. 1(b) is a photograph showing the appearance of the sheet obtained in Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] A. Starch-containing resin composition A-1. Overview of starch-containing resin composition The starch-containing resin composition of the present invention contains a thermoplastic resin, starch, and a lubricant for starch. The lubricant for starch is at least one selected from the group consisting of surfactants and plasticizers for starch. In one embodiment, the starch-containing resin composition further contains a water-soluble polysaccharide. The content of the starch in the starch-containing resin composition is 10% by weight to 70% by weight.

[0009] The starch-containing resin composition of the present invention contains starch with good dispersibility. The dispersibility of starch can be evaluated by the amount of starch aggregates confirmed by observing a press plate obtained from the starch-containing resin composition. When a press plate with a thickness of 0.1 mm is formed from the starch-containing resin composition of the present invention, the starch-containing resin composition has a surface area of ​​0.3 mm. 2 The above debris has an area of ​​2500 mm 2 The number of particles is 4 or less (preferably 3 or less, more preferably 2 or less) per range. The size of the foreign matter is judged based on the pulp-foreign matter measurement chart in accordance with JIS-P8208. Typically, the foreign matter may be a starch aggregate. Furthermore, by using the starch-containing resin composition of the present invention, a molded article with suppressed bleed-out can be obtained. More specifically, in the starch-containing resin composition of the present invention, the starch lubricant is unlikely to bleed out, and in the molded article obtained from the starch-containing resin composition, problems such as stickiness and printing defects can be prevented. These effects become even more remarkable by further adding a water-soluble polysaccharide to the starch-containing resin composition.

[0010] The starch-containing resin composition as described above can be obtained, for example, by forming a starch granule containing starch, a starch lubricant, and a water-soluble polysaccharide added as necessary, and then mixing the starch granule with a thermoplastic resin (for example, by mixing by melt kneading).

[0011] A-2. Starch As described above, the content of the starch in the starch-containing resin composition is 10% by weight to 70% by weight. In the present invention, the above-mentioned effects can be obtained even when a large amount of starch is contained. The content of the starch in the starch-containing resin composition is preferably 12% by weight to 60% by weight, more preferably 15% by weight to 50% by weight, and further preferably 20% by weight to 40% by weight. The content of the starch is based on the solid content of the starch-containing resin composition.

[0012] As the starch, any suitable starch can be used. Typically, the starch is added in powder form. The starch can be used alone or in combination of multiple types.

[0013] In one embodiment, the starch is raw starch, for example, starch obtained from corn, potato, tapioca, sweet potato, wheat, cassava, sago, sorghum, rice, beans, kudzu, bracken, lotus, water chestnut, etc.

[0014] In another embodiment, the starch is a modified starch. Examples of modified starches include physically modified starches (e.g., gelatinized starch, fractionated amylose, moist heat treated starch, etc.), enzymatically modified starches (e.g., hydrolyzed dextrin, enzymatically decomposed dextrin, amylose, etc.), chemically decomposed modified starches (e.g., acid treated starch, hypochlorite oxidized starch, dialdehyde starch, etc.), and chemically modified starch derivatives (e.g., esterified starch, etherified starch, cationized starch, crosslinked starch, etc.).

[0015] Examples of the esterified starch include acetate starch, succinate starch, nitrate starch, phosphate starch, urea phosphate starch, xanthate starch, and acetoacetate starch.

[0016] Examples of the etherified starch include allyl etherified starch, methyl etherified starch, carboxymethyl etherified starch, hydroxyethyl etherified starch, and hydroxypropyl etherified starch.

[0017] Examples of the crosslinked starch include formaldehyde crosslinked starch, epichlorohydrin crosslinked starch, phosphate crosslinked starch, acrolein crosslinked starch, and the like.

[0018] The above-mentioned pregelatinized starch is a starch in which raw starch having a crystalline structure (β structure) is broken down and changed to an amorphous structure (α structure) in a temperature environment of about 70°C or higher in the presence of an appropriate amount of moisture. This change from β structure to α structure when raw starch is heated with moisture is called "gelatinization". α structure starch is preferable because it has excellent dispersibility in thermoplastic resins compared to β structure. When the above-mentioned pregelatinized starch is left at a low temperature while still containing moisture, a phenomenon in which it returns to the original β structure crystalline state (called "aging") may occur. It is known that the α structure can be maintained by quickly removing moisture from the amorphous state of pregelatinized starch. Specifically, after heating in the presence of moisture to gelatinize it, the atmosphere is reduced in a vacuum device to obtain dehydrated α structure starch. In order for β-starch to become α-starch upon heating, it is generally considered preferable for the moisture content to be 17% or more.

[0019] In one embodiment, the average primary particle size of the starch is in the range of 1 μm to 100 μm, and representative examples include corn starch 15 μm, potato 50 μm, tapioca (cassava) 20 μm, rice 5 μm, wheat 10-20 μm, sweet potato 15 μm, sago 30 μm, and mung bean 20 μm. The average primary particle size of the starch is preferably 5 μm to 80 μm, more preferably 10 μm to 50 μm. If it is in such a range, a starch granule having excellent granulation productivity can be obtained. The average particle size of starch can be obtained by morphological observation under a microscope. That is, a photograph of the powder observed under a microscope is taken, and the arithmetic average (number average) of 50 randomly selected starches is obtained.

[0020] A-3.Starch lubricants As described above, the starch lubricant is at least one selected from the group consisting of surfactants and starch plasticizers.

[0021] The content of the starch lubricant is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 4 parts by weight, and even more preferably 0.1 to 3 parts by weight, based on 100 parts by weight of the solid content in the starch-containing resin composition. If the content is within such a range, the effects of the present invention are remarkable.

[0022] (Surfactant) The above surfactant is a compound composed of a hydrophobic group and a hydrophilic group, and the hydrophilic / hydrophobic balance can be controlled by adjusting the degree of esterification of the surfactant compound, the type of fatty acid (presence or absence of a hydroxyl group, saturated or unsaturated fatty acid, alkyl chain length), and the degree of polymerization. The above surfactant has the effect of imparting dispersibility, fluidity improvement, plasticization, lubricity, etc. to starch when obtaining a starch-containing resin composition.

[0023] The surfactant may be an emulsifier (eg, an emulsifier used as a food additive).

[0024] In one embodiment, the surfactant is at least one selected from the group consisting of polyhydric alcohol fatty acid esters, polyglycerin fatty acid esters, and alcohol esters of condensed hydroxy fatty acids.

[0025] The polyhydric alcohol fatty acid ester is an ester compound composed of a polyhydric alcohol and a fatty acid.

[0026] Examples of the polyhydric alcohol include alkane polyols such as pentaerythritol and glycerin, polyalkane polyols which are polymers of the alkane polyols, sugars such as sucrose, and sugar derivatives represented by sugar alcohols such as sorbitol and mannitol. These alcohols may be used alone or in combination of two or more.

[0027] Any appropriate fatty acid may be used as the fatty acid constituting the polyhydric alcohol fatty acid ester. In one embodiment, a fatty acid having 8 or more carbon atoms (preferably 8 to 24 carbon atoms, more preferably 10 to 22 carbon atoms) is used. Specific examples of the fatty acid include caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, nonadecanoic acid, arachic acid, gadoleic acid, eicosadienoic acid, arachidonic acid, behenic acid, erucic acid, docosadienoic acid, lignoceric acid, isostearic acid, ricinoleic acid, 12-hydroxystearic acid, 9-hydroxystearic acid, 10-hydroxystearic acid, and hydrogenated castor oil fatty acid (a fatty acid containing small amounts of stearic acid and palmitic acid in addition to 12-hydroxystearic acid). Palmitic acid and stearic acid are particularly preferred. The fatty acids may be used alone or in combination of two or more.

[0028] The polyhydric alcohol fatty acid ester can be obtained by esterification reaction of the polyhydric alcohol with a fatty acid. Specific examples of the polyhydric alcohol fatty acid ester include glycerin mono fatty acid ester, glycerin di fatty acid ester, fats and oils (coconut oil, palm oil, soybean oil, castor oil, etc.), hardened oils (hardened coconut oil, palm super hardened oil, etc.), sorbitan fatty acid ester, propylene glycol fatty acid ester, polyoxyethylene sorbitan fatty acid ester, sucrose fatty acid ester, glycerin diacetate monolaurate, diglycerin stearate, glycerin acetate fatty acid ester, glycerin lactate fatty acid ester, glycerin diacetyl tartaric acid fatty acid ester, etc., which are used as food emulsifiers. The polyhydric alcohol fatty acid ester may be used alone or in combination of two or more.

[0029] The polyglycerol fatty acid ester is an ester compound composed of polyglycerol and a fatty acid.

[0030] As the polyglycerin, any suitable polyglycerin can be used.Specific examples of the polyglycerin include diglycerin, triglycerin, tetraglycerin, pentaglycerin, hexaglycerin, heptaglycerin, octaglycerin, nonaglycerin, decaglycerin, eicosaglycerin, and tetracontaglycerin.Of these, diglycerin, triglycerin, pentaglycerin, or decaglycerin is preferred.Polyglycerin may be used alone or in combination of two or more.

[0031] Any appropriate fatty acid may be used as the fatty acid constituting the polyglycerol fatty acid ester. In one embodiment, a fatty acid having 8 or more carbon atoms (preferably 8 to 24 carbon atoms, more preferably 10 to 22 carbon atoms) is used. Specific examples of the fatty acid include caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, nonadecanoic acid, arachic acid, gadoleic acid, eicosadienoic acid, arachidonic acid, behenic acid, erucic acid, docosadienoic acid, lignoceric acid, isostearic acid, ricinoleic acid, 12-hydroxystearic acid, 9-hydroxystearic acid, 10-hydroxystearic acid, and hydrogenated castor oil fatty acid (a fatty acid containing small amounts of stearic acid and palmitic acid in addition to 12-hydroxystearic acid). Palmitic acid and stearic acid are particularly preferred. The fatty acids may be used alone or in combination of two or more.

[0032] Specific examples of the polyglycerol fatty acid ester include diglycerol palmitate, diglycerol stearate, diglycerol oleate, decaglycerol palmitate, decaglycerol stearate, decaglycerol oleate, etc. These may be used alone or in combination of two or more.

[0033] The fatty acid esterification rate of the polyglycerol fatty acid ester is preferably 35% or more, more preferably 50% to 70%. Within this range, a starch granule having excellent production stability can be obtained. In addition, the starch granule has excellent dispersibility in resins (especially thermoplastic resins). The esterification rate (%) is expressed by the formula: esterification rate (%) = (mol number of constituent fatty acids / number of hydroxyl groups of polyglycerol) x 100.

[0034] The polyglycerol fatty acid ester can be obtained by any suitable method. For example, it can be obtained by reacting polyglycerol with a fatty acid in the presence or absence of a catalyst (e.g., phosphoric acid, p-toluenesulfonic acid, caustic soda) at 100°C to 300°C (preferably 120°C to 260°C) while removing the generated water from the system. The reaction is preferably carried out in the presence of an inert gas. It may also be carried out in an azeotropic solvent such as toluene or xylene.

[0035] The alcohol ester of the condensed hydroxy fatty acid can be obtained by esterification reaction of the condensed hydroxy fatty acid with alcohol. The alcohol ester of the condensed hydroxy fatty acid can be obtained, for example, by mixing the condensed hydroxy fatty acid with alcohol, adding an alkali catalyst such as caustic soda or an acid catalyst such as phosphoric acid to the resulting mixture, and removing reaction water under heating. The progress of esterification during this reaction can be confirmed by measuring the acid value, saponification value, hydroxyl value, etc. Here, the condensed hydroxy fatty acid is a compound that can be obtained by dehydration condensation of hydroxy fatty acid. The condensed hydroxy fatty acid can be obtained, for example, by adding an alkali catalyst such as caustic soda to hydroxy fatty acid, and removing reaction water under heating to perform dehydration condensation.

[0036] The condensed hydroxy fatty acid is a condensation product of a hydroxy fatty acid, and the degree of condensation is preferably not less than 2, more preferably not less than 4. The upper limit of the degree of condensation of the condensed hydroxy fatty acid is, for example, 20. The degree of condensation can be calculated from the acid value of the raw hydroxy fatty acid and the acid value after the condensation reaction.

[0037] The above-mentioned hydroxy fatty acid is a fatty acid having one or more hydroxyl groups in the molecule.Specific examples of hydroxy fatty acid include ricinoleic acid, 12-hydroxystearic acid, savinic acid, 2-hydroxytetradecanoic acid, iprolic acid, 2-hydroxyhexadecanoic acid, yarapinolic acid, uniperilic acid, ambrettolic acid, aluritic acid, 2-hydroxyoctadecanoic acid, 18-hydroxyoctadecanoic acid, 9,10-dihydroxyoctadecanoic acid, camrolenoic acid, ferronic acid, and cerebronic acid.Hydroxy fatty acid may be used alone or in combination of two or more.

[0038] Examples of the alcohol include monohydric alcohols such as methyl alcohol, ethyl alcohol, and isopropyl alcohol; dihydric alcohols such as ethylene glycol and propylene glycol. In addition, polyhydric alcohols may be used as the alcohol. Examples of the polyhydric alcohol include alkane polyols such as pentaerythritol and glycerin; polyalkane polyols which are polymers of the alkane polyols; sugars such as sucrose; and sugar derivatives represented by sugar alcohols such as sorbitol and mannitol. These alcohols may be used alone or in combination of two or more.

[0039] Specific examples of the alcohol ester of the condensed hydroxy fatty acid include condensed ricinoleic acid hexaglycerin ester, which is an ester of condensed ricinoleic acid and hexaglycerin of glycerin 6 polymer, condensed ricinoleic acid tetraglycerin ester, which is an ester of condensed ricinoleic acid and tetraglycerin of glycerin 4 polymer, condensed 12-hydroxystearic acid propylene glycol ester, which is an ester of condensed 12-hydroxystearic acid and propylene glycol, and condensed linoleic acid propylene glycol ester, which is an ester of condensed ricinoleic acid and propylene glycol, etc. These may be used alone or in combination of two or more.

[0040] The alcohol ester of the condensed hydroxy may be a commercially available product. Examples of the commercially available product include "Tirabazole P-4", "Tirabazole VR-01", "Tirabazole VR-08", and "Tirabazole H-818" manufactured by Taiyo Kagaku Co., Ltd.

[0041] The content of the surfactant is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 4 parts by weight, and further preferably 0.1 to 3 parts by weight, based on 100 parts by weight of the solid content in the starch-containing resin composition. If the content is within such a range, the effects of the present invention are remarkable.

[0042] (Starch plasticizer) A starch plasticizer refers to a compound that is incorporated into the molecular structure of starch, compatibilizes it, and provides the effect of imparting flexibility, fluidity, etc. In this specification, water is not considered to be a starch plasticizer.

[0043] Specific examples of the starch plasticizer include high-boiling alcohols such as n-octyl alcohol, isodecyl alcohol, and n-decyl alcohol, polyhydric alcohols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, propanediol, 1,3-butanediol, glycerin, diglycerin, trimethylolpropane, pentaerythritol, 3-methyl-1,3,5-pentatriol, and sorbitol, and polyalkylene oxides such as polyethylene glycol, polypropylene glycol, polyglycerin, and ethylene glycol-propylene glycol copolymers. In one embodiment, the starch plasticizer is at least one selected from the group consisting of ethylene glycol, propylene glycol, glycerin, and sorbitol.

[0044] Another example of the starch plasticizer is low molecular weight aliphatic polyester. Examples of low molecular weight aliphatic polyester include polycondensates of diols such as ethylene glycol and butylene glycol with dicarboxylic acids such as adipic acid and succinic acid; and hydroxyalkanoates made of low polymers such as caprolactone, lactic acid, and hydroxybutyric acid. Among them, low molecular weight aliphatic polyesters formed by esterifying terminal carboxylic acids with alcohols having 2 to 8 carbon atoms are preferably used.

[0045] The content of the starch plasticizer is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 4 parts by weight, and further preferably 0.1 to 3 parts by weight, based on 100 parts by weight of the solid content in the starch-containing resin composition. If it is within such a range, the above-mentioned effects of the present invention become remarkable.

[0046] A-4.Water-soluble polysaccharide The water-soluble polysaccharides refer to water-soluble compounds that are composed of long chains of monosaccharides such as glucose and mannose. In one embodiment, the water-soluble polysaccharides are water-soluble carbohydrates that are composed of 10 or more monosaccharides bonded together. The water-soluble polysaccharides impart moisture retention to starch and promote gelatinization, and as a result, good dispersibility of starch can be obtained when melt-kneaded with a thermoplastic resin.

[0047] In one embodiment, the water-soluble polysaccharide may be a polymeric substance of natural origin, such as a water-soluble polysaccharide derived from a plant (seed, sap, fruit, etc.), seaweed, or microorganism.

[0048] Specific examples of the water-soluble polysaccharides include pullulan, dextrin, chitosan, tamarind seed gum, guar gum, locust bean gum, gum arabic, karaya gum, pectin, cellulose, konjac mannan, soybean polysaccharides, carrageenan, agar, tragacanth gum, alginic acid, xanthan gum, gellan gum, Agrobacterium succinoglycan, carboxymethylcellulose, cationized guar gum, etc. Among these, pullulan or dextrin is preferred, and pullulan is more preferred. The water-soluble polysaccharides may be used alone or in combination of two or more.

[0049] Dextrin is a low molecular weight carbohydrate obtained by hydrolysis of starch or glycogen. Depending on the degree of saccharification (DE) of starch, it is classified into powdered candy (DE of about 20-40), maltodextrin (DE of about 10-20), and dextrin (DE of 10 or less).

[0050] The pullulan is a polysaccharide consisting of glucose alone. Pullulan is a plant-derived microbial fermentation product made from starch, and is water-soluble and has characteristics such as water retention, thickening, lubricity, adhesion, binding, and film properties. Pullulan is particularly preferred because it has a thermal decomposition temperature of around 290°C and has heat resistance suitable for use in thermoplastic resins.

[0051] The content of the water-soluble polysaccharide is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 4 parts by weight, and even more preferably 0.1 to 3 parts by weight, based on 100 parts by weight of the solid content in the starch-containing resin composition. If the content is within such a range, the effects of the present invention are remarkable.

[0052] A-5. Thermoplastic resin Any suitable thermoplastic resin can be used as the thermoplastic resin. In one embodiment, a thermoplastic resin having a processable temperature of 200° C. or less, preferably 180° C. or less is preferably used. By using such a thermoplastic resin, the starch-containing resin composition can be prepared at a temperature at which starch is unlikely to deteriorate.

[0053] Specific examples of the thermoplastic resin include high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), polypropylene (PP), polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polystyrene (PS), high impact polystyrene (HIPS), styrene-butadiene copolymer, styrene-butadiene elastomer (SBS), hydrogenated styrene-butadiene elastomer (SEBS), styrene-isoprene elastomer (SIS), hydrogenated styrene-isoprene elastomer (SEPS), polyolefin elastomer (TPO), polyvinyl acetate (PVAc), ABS resin (acrylonitrile butadiene styrene resin), AS resin, acrylic resin (PMMA), etc.

[0054] In addition, a biodegradable resin may be used as the resin. Examples of the biodegradable resin include aliphatic polyester resins (e.g., homopolymers or copolymers of polycaprolactone, polylactic acid, polyethylene succinate, polybutylene succinate-adipate, polyhydroxyvalerate, etc., and modified homopolymers or copolymers thereof), aliphatic / aromatic polyester resins (e.g., block polymers or random polymers of aliphatic carboxylic acids or hydroxy acids, aromatic dicarboxylic acids and 1,3-propanediol, etc.), and polyvinyl alcohol resins (e.g., polyvinyl alcohol, polyvinyl acetate, polyvinyl butyrate, ethylene-vinyl alcohol copolymers, etc.). Examples of naturally derived biodegradable resins include natural rubber. By using the starch granules in a biodegradable resin and blending starch, the mechanical properties, bio content, and biodegradation rate of the resin can be adjusted according to the application, and the resin can be used alone or in combination of two or more kinds, or in combination with an olefin resin.

[0055] The content of the thermoplastic resin is preferably 86 to 40 parts by weight, more preferably 85 to 50 parts by weight, and further preferably 80 to 60 parts by weight, based on 100 parts by weight of the solid content in the starch-containing resin composition. If the content is within such a range, the effects of the present invention are remarkable.

[0056] A-6. Other ingredients The starch-containing resin composition may further contain any appropriate other components (additives) as necessary. Examples of additives include antioxidants, light stabilizers, foaming agents, UV absorbers, foaming agents, antiblocking agents, heat stabilizers, impact modifiers, antibacterial agents, compatibilizers, plasticizers, tackifiers, processing aids, lubricants, coupling agents, flame retardants, oxygen scavengers, colorants, etc. The additives may be added at any appropriate timing in the manufacturing process of the starch-containing resin composition, for example, in the form of liquid, powder, pellets, granules, or master batch.

[0057] In one embodiment, the starch-containing resin composition further includes a compatibilizer. By adding the compatibilizer, the compatibility between the thermoplastic resin and the starch is increased, and as a result, the dispersibility of the starch can be improved.

[0058] Examples of the compatibilizer include saturated carboxylic acids, unsaturated carboxylic acids, and derivatives thereof; unsaturated carboxylic acids; and thermoplastic resins modified with derivatives of unsaturated carboxylic acids.

[0059] Examples of the saturated carboxylic acid include succinic anhydride, phthalic anhydride, phthalic acid, tetrahydrophthalic anhydride, and adipic anhydride.

[0060] Examples of the unsaturated carboxylic acid include maleic anhydride, maleic acid, nadic anhydride, itaconic anhydride, itaconic acid, citraconic anhydride, citraconic acid, crotonic acid, isocrotonic acid, mesaconic acid, angelic acid, sorbic acid, and acrylic acid.

[0061] Examples of the derivative of the saturated carboxylic acid include metal salts, amides, imides, esters, etc. of unsaturated carboxylic acids. Examples of the thermoplastic resin in the thermoplastic resin modified with a derivative of an unsaturated carboxylic acid include low-density polyethylene, ethylene-α-olefin copolymer, high-density polyethylene, polypropylene, propylene block copolymer, propylene random copolymer, etc.

[0062] In one embodiment, the starch-containing resin composition further contains trehalose. By adding trehalose, deterioration of starch in the starch-containing resin composition over time can be suppressed.

[0063] B. Method for Producing Starch-Containing Resin Composition In one embodiment, the starch-containing resin composition can be obtained by melt-kneading the thermoplastic resin, the starch, the starch lubricant, and a water-soluble polysaccharide added as necessary. Any appropriate method can be adopted as the melt-kneading method. For example, a kneader, a Banbury mixer, a roll, or a single-screw or multi-screw extruder having two or more screws can be used. A twin-screw extruder is preferably used. The melt-kneaded composition can be pelletized. In one embodiment, the melt-kneading is performed in a temperature range of 80°C to 170°C (preferably 100°C to 160°C).

[0064] In one embodiment, a starch granule containing the starch, the starch lubricant, and a water-soluble polysaccharide added as necessary is obtained, and then the starch granule is melt-kneaded with a thermoplastic resin to obtain a starch-containing resin composition. By adopting such a production method, a starch-containing resin composition having a high starch content can be obtained with high productivity. Specifically, since the starch granule has a remarkably excellent stability when put into an apparatus such as an extruder, the productivity (compound processing speed per hour) of the starch-containing resin composition can be dramatically improved by using the starch granule.

[0065] (Starch granules) The starch granules can be produced by any suitable method. The starch granules can be obtained, for example, by subjecting a mixture containing the starch, the starch lubricant, and a water-soluble polysaccharide added as needed to a semi-wet granulation method. In one embodiment, the method for producing the starch granules includes a mixing step of mixing the starch, the starch lubricant, and a water-soluble polysaccharide added as needed, and a granulation step of obtaining a granule from the mixture obtained through the mixing step. In the mixing step, water may be further mixed. The starch, water-soluble polysaccharide, and starch lubricant described in Section A can be used.

[0066] The content of the starch lubricant is preferably 0.1 to 10 parts by weight, more preferably 0.1 to 7 parts by weight, even more preferably 0.2 to 5 parts by weight, particularly preferably 0.3 to 5 parts by weight, and most preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of starch. If the content is within such a range, the effects of the present invention are remarkable.

[0067] The content of the water-soluble polysaccharide is preferably 0.1 to 10 parts by weight, more preferably 0.1 to 7 parts by weight, even more preferably 0.2 to 5 parts by weight, particularly preferably 0.3 to 5 parts by weight, and most preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of the starch. If it is within such a range, the effects of the present invention will be remarkable.

[0068] The water to be added is not particularly limited, and for example, tap water, distilled water, ion-exchanged water, hard water, soft water, etc. can be used.

[0069] In the above mixing step, the amount of water to be added is usually 1 to 30 parts by weight, preferably 2 to 20 parts by weight, and more preferably 3 to 17 parts by weight, relative to 100 parts by weight of starch. Note that, although the starch powder used as a raw material in the starch granules of the present invention may contain a certain amount of moisture, the above amount of water is the number of parts added excluding the amount of moisture contained in the raw starch powder.

[0070] In one embodiment, the amount of water in the mixing step is adjusted according to the amount of the water-soluble polysaccharide, for example, 1 to 30 parts by weight, preferably 3 to 25 parts by weight, and more preferably 5 to 20 parts by weight, per 1 part by weight of the water-soluble polysaccharide.

[0071] In one embodiment, in the mixing step, powdery raw materials (starch, water-soluble polysaccharides, starch lubricant (surfactant and / or starch plasticizer), and other additives) are mixed to obtain a powder mixture; liquid raw materials (water, starch lubricant (surfactant or starch plasticizer)) are mixed separately to obtain a mixed liquid (which may be a suspension dispersion); and then the mixed liquid is gradually mixed into the powder mixture. In this way, the mixing time can be shortened. For example, the water-soluble polysaccharides can be mixed as an aqueous solution in which they are dissolved in water in advance, but the solution viscosity of the polysaccharide aqueous solution becomes too high, so it becomes necessary to extend the mixing time.

[0072] The mixture obtained in the above mixing step exhibits sufficient and highly homogeneous binding strength as a binder because the water-soluble polysaccharide can uniformly cover the surface of the starch particles over a wide area, which significantly improves the granulation property and productivity of the starch granules, and allows the obtained granules to exhibit appropriate hardness (shape retention) and reduce fine powder.

[0073] In the mixing step, it is preferable to mix the components at room temperature and homogenize them using any suitable mixer, such as a Henschel mixer, a powder kneader (KDH, KDA, CKD, CPM) (Dalton), a Spartan mixer (SPM) (Dalton), or a SP granulator (SPG) (Dalton).

[0074] The mixing time in the mixing step can be any appropriate time depending on the type of components, the type of mixer, the component blending ratio, etc. Preferably, the mixing time is set so that the surface of the starch is sufficiently and uniformly covered with the aqueous polysaccharide solution. With a high-speed mixer such as a Henschel mixer or a Spartan mixer, the mixing can be carried out within a processing time of 1 to 10 minutes. On the other hand, with a powder kneader, a processing time of several minutes to 60 minutes may be required.

[0075] In the granulation step, a compression granulation method is preferably used. In addition, in the granulation step, a semi-wet granulation method can be preferably used. Examples of the compression granulation method / semi-wet granulation method include a disk pelleter method, a double granulation method, and a briquetting method. From the viewpoint of the balance between productivity and the quality of the obtained starch granules, the disk pelleter method is preferably used.

[0076] The basic structure of the disk pelletizer is one or two disks with many holes of 2mm to 30mm, and a roller for pressure-feeding the raw material into the holes of the disk. The raw material supplied between the disk and the roller, or between two disks, is pressed into the holes of the disk as the roller rotates, and a cylindrical extrudate is formed. Here, the disk holes are tapered, and a compressive stress is applied from the outer periphery of the die hole in the process of the starch mixture passing through the holes. The length of this tapered hole is called the effective length. The extruded granule precursor is cut by a cutter or the like on the back side of the disk to obtain a pellet-shaped starch granule. The length of the granule can be adjusted by the distance between the back side of the disk and the cutter and the number of rotations of the roller. More specifically, the disc pelleter type includes a roller disc die type, a roller ring die type, a double die type, a flat die type, etc. An example of a commercially available disc pelleter type granulator is the Disc Pelletter F Series manufactured by Dalton.

[0077] Although disk pelletizers do not usually have a heating / cooling system, they do heat up due to shear heat generated during operation. In the granulation process, if the temperature during granulation reaches the gelatinization temperature of starch (approximately 70°C or higher), starch may gelatinize, making granulation difficult. In order to prevent starch from gelatinizing due to shear heat generated during granulation, it is preferable to cool the disk pelletizer by installing a cooling jacket as necessary, and it is preferable to control the granulation temperature to preferably 60°C or less, more preferably 55°C or less, and even more preferably 50°C or less.

[0078] In the granulation step, the granules (or granule precursor) may be dried as necessary to optimize the moisture content. Any appropriate method can be used as the drying method. In addition, a process such as a vibrating sieve can be carried out before or after drying the granules to obtain starch granules from which fine powder has been removed. Any appropriate drying equipment can be used for drying. For example, a vibrating fluidized dryer is preferred because it can perform drying efficiently in a short time, and examples of such devices include the VDF series vibrating fluidized dryers manufactured by Dalton.

[0079] In the present invention, various molded articles are provided using the above-mentioned polylactic acid resin composition. For example, injection molded articles, extrusion molded articles, sheets, films, foam molded articles, etc. can be provided. In addition, shaped articles (sheet-shaped shaped articles) can be obtained from the above-mentioned sheets. EXAMPLES

[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, parts and percentages are based on weight unless otherwise specified.

[0081] [Production Example 1] Production of starch granules MB-1 A powder kneader (manufactured by Dalton, product name "KDHJ-10"; processing capacity: 6 L) was charged with 100 parts by weight of starch (manufactured by Sanwa Starch Kogyo Co., Ltd., raw starch made from corn, product name "Corn Starch Y"; in the table, "B-1"), 1 part by weight of pullulan, a water-soluble polysaccharide (manufactured by Hayashibara Co., Ltd.; in the table, "E-1"), and 1 part by weight of trehalose (manufactured by Hayashibara Co., Ltd.; in the table, "F-1") as an additional component, and the mixture was stirred for 6 minutes while rotating the stirring blade at a rotation speed of 30 rpm to obtain powder mixture A. Separately, 13 parts of water, 2 parts by weight of polyglycerol condensed hydroxy fatty acid ester (manufactured by Taiyo Kagaku Co., Ltd., product name ``Chirabazole H818''; in the table, ``C-1'') as a surfactant, and 2 parts by weight of glycerin (manufactured by Hayashi Pure Chemical Industries, Ltd., in the table, ``D-1'') as a starch plasticizer were weighed into a 1 L plastic container and thoroughly stirred at room temperature to obtain aqueous dispersion mixture B. Water-dispersed mixture B was gradually added to powder mixture A in a powder kneader while stirring with a stirring blade at a rotation speed of 30 rpm. After the entire amount of water-dispersed mixture B was mixed, stirring was continued for an additional 6 minutes to obtain a mixture of powder mixture A and water-dispersed mixture B (mixture C). Mixture C was put into a disk pelleter (manufactured by Dalton, product name "Disc Pelleter F-5 / 11-175; capacity: 5 L") to obtain a pellet-shaped starch granule. At this time, the die hole diameter was set to 3 mmφ, the die plate thickness was set to 15 mm, the effective length of the die hole was set to 10 mm, and the rotation speed of the roller of the disk pelleter was set to 108 rpm to obtain a starch granule (MB-1). The temperature of the resulting starch granules (MB-1) immediately after granulation was measured with a contact thermocouple and found to be 55°C. The amount of moisture (unit: weight%) remaining in the starch granules was measured using an infrared moisture meter (FD-660, manufactured by Kett Electric Laboratory). The moisture content was found to be 23.4% by weight.

[0082] [Production Examples 2 to 6] Production of starch granules MB-2 to MB-6 Starch granules MB-2 to MB-6 were obtained in the same manner as in Example 1, except that the starch, starch lubricant (surfactant and / or starch plasticizer), water-soluble polysaccharide, and other components shown in Table 1 were used in the amounts shown in Table 1 (units in the table: parts by weight). The specific details of each component used in Production Examples 1 to 6 are as shown in Table 3. The composition ratios in Table 1 indicate the feed composition when producing starch granules. Table 2 shows the composition ratio (wt%) of the starch granules, which was calculated from the blending ratio after measuring the moisture content of the final starch granules and subtracting the moisture content. The starch composition ratio in Table 2 is the composition ratio of "dry starch." When the moisture content of the starch raw materials, Corn Starch Y "B-1" and Corn Alpha Y "B-2", was measured using the infrared moisture meter, both were 13 wt%.

[0083] [Table 1]

[0084] [Table 2]

[0085] [Table 3]

[0086] [Example 1] 60 parts by weight of PBAT resin (manufactured by BASF, product name "Ecoflex F Blend C1200", MFR 3.8g / 10min; in the table, "A-1") and 40 parts by weight of starch granules (MB-1) were charged into a twin-screw extruder (manufactured by Toshiba Machine Co., Ltd., product name "TEM37SS", L / D=48) and continuously melt-kneaded to produce pellets of a starch-containing resin composition. The PBAT resin and the starch granules MB-1 were each independently quantitatively fed into the twin-screw extruder at the hopper position at the most upstream part of the extruder via a gravimetric feeder. The cylinder temperatures of the extruder were set to 140°C in the front stage, 120°C in the middle stage, and 140°C in the rear stage. An open vent was provided at the top of the barrel in the midstream section of the extruder to allow open devolatilization, and two vents were provided at two locations at the top of the barrel in the downstream section to allow devolatilization under reduced pressure of -90 kPa. The twin-screw extruder settings (discharge speed, main screw rotation speed, extruder load, molten resin temperature) are as shown in Table 4. The melt-kneaded resin composition was extruded in the form of strands from a two-hole die opening of 3 mmφ, cooled in a water-cooled bath, and formed into pellets of approximately 3 mm in length. The details of the settings are as follows: <Twin-screw extruder setting conditions> (a) Resin composition discharge speed (unit: kg / Hr) It is the amount of compound resin composition discharged per hour. (b) Extruder screw rotation speed (unit: rpm) The screw rotation speed of the twin-screw extruder. (c) Extruder load (unit: %) This is the displayed value of the actual measured power load percentage (percentage of the maximum allowable motor load) of a twin screw extruder or single screw extruder. (d) Temperature of molten resin at the die (unit: °C) The temperature of the resin composition extruded from the die was measured with a contact thermocouple.

[0087] [Examples 2 and 3] As shown in Table 4, pellets of starch-containing resin composition were obtained in the same manner as in Example 1, except that the blending ratio of PBAT resin and starch granules MB-1 was changed.

[0088] [Example 4] Pellets of a starch-containing resin composition were obtained in the same manner as in Example 1, except that polylactic acid (PLA; Nature Works, Inc., product name "Ingeo 4032D"; melting point 155 to 170°C; "A-2" in the table) was used instead of the PBAT resin, and the cylinder temperature of the extruder was set to 200°C from the middle stage onwards.

[0089] [Examples 5 to 9] Pellets of a starch-containing resin composition were obtained in the same manner as in Example 1, except that the starch granules shown in Table 4 were used in the amounts shown in Table 4.

[0090] [Example 10] As shown in Table 2, pellets of a starch-containing resin composition were obtained in the same manner as in Example 1, except that the setting conditions of the twin-screw extruder were changed. In Example 10, the discharge rate was set to 40 kg / Hr, which was twice that of Example 1, and a resin composition with excellent starch dispersibility was obtained.

[0091] [Example 11] Similarly to Production Example 1, 100 parts by weight of starch "B-1" and 1 part by weight of trehalose "F-1" were added to prepare powder mixture A. Separately, 7 parts of water, 2 parts by weight of polyglycerol condensed hydroxy fatty acid ester "C-1", and 2 parts by weight of glycerin "D-1" were weighed into a 1 L plastic container and thoroughly stirred at room temperature to obtain water-dispersed mixture B. Water-dispersed mixture B was gradually added to powder mixture A in a powder kneader while stirring with a stirring blade at a rotation speed of 30 rpm. After the entire amount of water-dispersed mixture B was mixed, stirring was continued for an additional 6 minutes to obtain a mixture of powder mixture A and water-dispersed mixture B (mixture C). Except for replacing this mixture C with starch granules (MB-1), the mixture was fed into a twin-screw extruder in the compounding ratio shown in Table 4 in the same manner as in Example 1, and continuously melt-kneaded to produce pellets of a starch-containing resin composition.

[0092] [Comparative Example 1] A mixture containing 60 parts by weight of PBAT resin "A-1", 40 parts by weight of starch powder "B-1", and 6 parts by weight of water was charged into a twin-screw extruder and continuously melt-kneaded to produce pellets of a starch-containing resin composition. The mixture was fed from the top of the extruder. The discharge rate and the main screw speed were the same as in Example 1. The resulting starch resin composition contained many aggregates of starch powder.

[0093] [Comparative Example 2] Pellets of a starch-containing resin composition were produced in the same manner as in Comparative Example 1, except that the discharge rate was set to 30 kg / Hr. However, a bridge of the starch powder "B-1" occurred at the raw material inlet, and the material did not penetrate the extruder properly when fed into the extruder, making it impossible to obtain stable pellets. In the present invention, by preparing a starch-containing resin composition with a predetermined composition, the starch feedneck can be eliminated, and the starch-containing resin composition can be obtained with high productivity. Also, a starch-containing resin composition having excellent dispersibility of starch can be obtained.

[0094] [Reference example 1] The evaluation results of PBAT resin "A-1" are shown.

[0095] <Evaluation> The starch-containing resin compositions obtained in the Examples and Comparative Examples, and Reference Example 1 were subjected to the following evaluations. The results are shown in Table 4. (1) Dispersibility of starch in resin composition The pellets of the resin composition were rolled in a hot press to form a sheet with an area of ​​50 mm x 50 mm and a thickness of about 0.1 mm. The sheet was visually observed through which the presence of starch aggregates was evaluated according to the following criteria. AA: Good dispersion state with almost no starch agglomerates observed (based on the pulp-impurity measurement chart in accordance with JIS-P8208, 0.3 mm 2 (The number of starch aggregates having a projected cross-sectional area of ​​4 or less) A: A state in which a small amount of relatively small starch aggregates remain (above 0.3 mm) 2 (The number of starch aggregates having a projected cross-sectional area of ​​5 or more but less than 10) BB: A state in which a considerable number of relatively small starch aggregates remain (above 0.3 mm 2 (The number of starch aggregates having a projected cross-sectional area of ​​10 or more but less than 20) B: State in which starch aggregates are large (the number of starch aggregates having a projected cross-sectional area of ​​0.3 mm2 or more is 20 or more) (Distribution order: AA>A>BB>B (left good)) Photographs of the appearance of the above-mentioned sheets in Examples 1 and 4 are shown in FIG. (2) Bleeding out in resin composition The sheet having a thickness of about 0.1 mm used in the evaluation of the dispersibility of starch described above was left at room temperature for one month, and the presence or absence of bleeding on the surface of the sheet was visually observed and evaluated according to the following criteria. AA: No bleeding observed on the sheet surface A: A very small amount of bleeding is observed on the sheet surface. BB: Some bleeding is observed on the sheet surface. B: Bleeding is clearly observed on the sheet surface. (Bleed-out ranking: AA>A>BB>B (left good)) (3) MFR in resin composition (unit: g / 10 min) Using pellets of the resin composition, the MFR was measured under the following conditions (in accordance with ISO1133). PBAT resin: 190℃, 5kg load PLA resin: 190℃, 2.16kg load (4) Tensile measurement The tensile strength at break (unit: MPa) and elongation at break (unit: %) of the starch-containing resin composition were measured at a pulling speed of 5 mm / min in accordance with ISO527. For the test pieces to be measured, pellets of the resin composition were dried at 90°C for 10 hours, and then an injection molding machine (SI-80W manufactured by Toyo Machinery & Metals Co., Ltd.) was used to mold dumbbell-shaped test pieces (1A type multipurpose test pieces). The molding conditions for the PBAT resin composition (including Reference Example 1) were a cylinder set temperature of 150°C, a mold temperature of 40°C (both fixed side and moving side), and a cooling time of 30 seconds, while for the PLA resin composition (Example 4), the cylinder set temperature was 200°C, a mold temperature of 110°C (both fixed side and moving side), and a cooling time of 160 seconds to mold the dumbbell-shaped test pieces. (5) Specific gravity The specific gravity of the resin composition was measured using a specific gravity meter (DMA220H, manufactured by Shinko Denshi Co., Ltd.).

[0096] [Table 4]

[0097] As is clear from Table 4, according to the present invention, a resin composition which contains starch at a high concentration and yet has excellent starch dispersibility can be obtained with high productivity.

Claims

1. A method for producing a thermoplastic resin composition comprising melt-kneading a thermoplastic resin and a starch granule, The starch granules contain starch, a starch lubricant, and a water-soluble polysaccharide; the content of the water-soluble polysaccharide is 0.1 to 10 parts by weight based on 100 parts by weight of the starch; A method for producing a starch-containing resin composition, wherein the content of the starch lubricant is 0.1 to 10 parts by weight based on 100 parts by weight of the starch, The content of the starch in the starch-containing resin composition is 10% by weight to 70% by weight, When a press plate having a thickness of 0.1 mm is formed from the starch-containing resin composition, a thickness of 0.3 mm or less is observed on the surface of the press plate. 2 The above debris has an area of ​​2500 mm 2 There will be no more than four per range. A method for producing a starch-containing resin composition.

2. A method for producing a starch-containing resin composition as described in claim 1, wherein the content of the water-soluble polysaccharide in the starch-containing resin composition is 0.01 parts by weight to 5 parts by weight per 100 parts by weight of solids in the starch-containing resin composition.

3. 3. The method for producing a starch-containing resin composition according to claim 1, wherein the water-soluble polysaccharide is at least one selected from the group consisting of pullulan and dextrin.

4. A method for producing a starch-containing resin composition described in any of claims 1 to 3, wherein the content of the starch lubricant in the starch-containing resin composition is 0.01 parts by weight to 5 parts by weight per 100 parts by weight of solids in the starch-containing resin composition.

5. The starch lubricant is a surfactant, 5. The method for producing a starch-containing resin composition according to claim 1, wherein the surfactant is at least one selected from the group consisting of polyhydric alcohol fatty acid esters, polyglycerol fatty acid esters and alcohol esters of condensed hydroxy fatty acids.

6. The starch lubricant is a starch plasticizer, 6. The method for producing a starch-containing resin composition according to claim 1, wherein the starch plasticizer is at least one selected from the group consisting of ethylene glycol, propylene glycol, glycerin and sorbitol.

7. The method for producing a starch-containing resin composition according to claim 1 , wherein the starch is a pregelatinized starch.

8. A method for producing a starch-containing resin composition described in any of claims 1 to 7, wherein the starch granules are obtained by subjecting a mixture containing the starch, the starch lubricant, and the water-soluble polysaccharide to a semi-wet granulation method.

9. The starch granules, a mixing step of mixing the starch, the starch lubricant, and a water-soluble polysaccharide; A granulation step of obtaining a granulated product from the mixture obtained through the mixing step. A method for producing the starch-containing resin composition according to any one of claims 1 to 8, which is obtained by the method.

10. A method for producing a starch-containing resin composition as described in claim 9, wherein a compression granulation method or a semi-wet granulation method is used in the granulation process.

Citation Information

Patent Citations

  • Material based on starch

    JP1995070205A

  • Highly strong biodegradable resin composition and molded article

    JP2003073539A

  • Resin composition

    JP2009120651A

  • Biodegradable resin composition and biodegradable resin film

    JP2009167370A

  • Resin composition, film, bag product, and method for producing resin composition

    JP2011026538A